Analysis the Effects Macroprudential Policies Through Macroeconomic Variables on Housing Credit Growth - Indrayanti, Shinta Hervi; Kornitasari, Yenny (Contemporary Studies in Economic, Finance and Banking, 2025)
The increase in population without accompanied development and provision of affordable housing will become a major problem due to the unfulfilled need for housing. The increasing demand causes a surge in housing prices. With this problem, banks as intermediary institutions develop their activities by providing facilities to meet housing needs through Home Ownership Credit (KPR) products. This study aims to determine the effect of macroprudential policy through macroeconomic variables (JUB, IHPR, Inflation, and Economic Growth) on housing credit growth in Indonesia from 2005-2023. The method used is Multiple Linear Regression Analysis, with interest rates as a control variable. There is a need to control credit growth to prevent a surge in housing asset prices and maintain inflation to remain under control, thus creating financial system stability. The results of this study indicate that the first objective of macroprudential policy has a significant effect on credit growth. In addition, the second objective of the macroprudential policy through variables such as JUB, Inflation, Economic Growth, and Interest Rates has a significant effect on housing credit growth. Meanwhile, through the IHPR variable, it does not affect credit growth.